An Analysis Of Feminism In “Colette” Movie Script By Wash Westmoreland - Selvira Tatawalat; Sri Winarsih; Marnina Marnina (Musamus Journal of Language and Literature, 2023)
This research examines feminism as fought by women. Feminism is a movement that fights for equality between men and women. In this case, women want equal rights and opportunities in every aspect that men have. This research focuses on the types of feminism and women’s rights that fought by women in France in the 18th century. This research is a qualitative research and the method used in this research is a qualitative descriptive method. In addition, the theories used in this research have two theories. The first theory was the theory of feminism proposed by Rosemarie Tong to analyze the types of feminism found in Colette movie script. The second theory is the theory of women’s rights proposed by Sophie Mousset to analyze the rights of women fought by the main character in the Colette movie. The results of this research indicate that there are several types of feminism experienced by the main character. There are five types of feminism, they are Liberal feminism, Radical feminism, Anarchist feminism, Marxist feminism and Socialist Feminism. Moreover, there are women’s rights that are found in this movie. There are four women’s rights, they are Right to work, Freedom from slavery, Right to own property, and Right to own literary and artistic production.